A modified artificial bee colony algorithm with its applications in signal processing. (6th June 2013) - Yu, Xiangyu; Zhu, Zucong
Artificial bee colony (ABC) algorithm is a biological–inspired optimisation algorithm proposed in recent years. It has been shown to have some advantages than most of conventional biological–inspired algorithms and has been widely used in many applications. However, the ABC algorithm does not consider the balance between global best and local best, and make ABC algorithm insufficiency. In this paper, a modified ABC algorithm is proposed, global best is introduced into the original ABC algorithm to modify the update equation of employed and onlooker bees while the equation for scouts remain unchanged. The effectiveness of the proposed approach is verified on the problem of peak–to–average power ratio reduction in orthogonal frequency division multiplexing signals and multi–level image segmentation. Simulation results showed that the proposed approach has better performance than traditional ABC algorithm with the same computational complexity.